Visionary Leadership and Teacher Professionalism: A Managerial Analysis in Islamic Education - Muhammad Zaid Arsyad; Hisyam Umar Altuwy; Zaki Ulien Nuha; Maryono Maryono (Jurnal Manajemen Pendidikan Islam Darussalam, 2026)
This study explores the practice of visionary leadership in madrasah management and its implications for strengthening teacher professionalism within Islamic education. Visionary leadership is understood as the ability of educational leaders to formulate institutional vision, translate it into managerial policies, and strategically manage resources to support institutional quality and sustainable professional development. Using a qualitative case study approach, this research was conducted in December 2025 at an Islamic educational institution in Indonesia. Data were obtained from two key informants a foundation administrator and a madrasah principal supported by institutional documents. Data collection involved in depth interviews, limited observation, and documentation, while analysis was conducted thematically through data reduction, data display, and conclusion drawing with source triangulation to ensure credibility. The findings indicate that visionary leadership, when implemented through integrated managerial functions such as program planning, organizational structuring, teacher mobilization, academic supervision, and systematic evaluation, significantly strengthens teachers’ professional commitment, improves instructional performance, and supports sustainable professional growth. The novelty of this study lies in demonstrating that visionary leadership in madrasahs operates not merely as a normative leadership orientation but as a value based managerial practice grounded in Islamic principles that links institutional vision, ethical values, and professional development. This integrative model illustrates how leadership vision is operationalized in daily managerial practices to enhance institutional effectiveness and teacher professionalism, providing theoretical and practical insights for madrasah leaders, policymakers, and educational practitioners in developing vision oriented leadership strategies for sustainable improvement in Islamic education